2003
DOI: 10.4028/www.scientific.net/kem.254-256.351
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Bone-Like Apatite Formation on Calcium Phosphate Ceramics in Different Simulated Body Fluids (SBF)

Abstract: Five kinds of simulated body fluids were prepared according to the Ca 2+ ions concentration in body fluids of human, dog, pig, rabbit and monkey so that the different biological environments in different animals were simulated. Results showed that Ca 2+ can induce bone-like apatite formation in a dose-dependent manner; there is a threshold of Ca 2+ local concentration for the formation of bone-like apatite. The threshold of Ca 2+ for bone-like apatite formation in static stimulated body fluid (SBF) is differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…The MCPP sample obviously contained a greater mineralized layer than the others. The 21 represented hydroxyl. Additionally, the XRD analysis on the doped CPP surface with mineral deposit for 28-day degradation in Figure 6 also indicated the characteristic peaks of HA in (211), (112), (300), and (202).…”
Section: Analysis On Mineralization and Mineralizedmentioning
confidence: 99%
See 2 more Smart Citations
“…The MCPP sample obviously contained a greater mineralized layer than the others. The 21 represented hydroxyl. Additionally, the XRD analysis on the doped CPP surface with mineral deposit for 28-day degradation in Figure 6 also indicated the characteristic peaks of HA in (211), (112), (300), and (202).…”
Section: Analysis On Mineralization and Mineralizedmentioning
confidence: 99%
“…The crystal lattice parameters in Table II were calculated by curve fitting and indicated Na 1 , Mg 21 , Zn 21 substituting in the site of Ca 21 and the cell volumes of Na-, Mg-, and Zn-doped CPP shrank while those of K-and Sr-doped CPP expanded. Figure 2 shows the XPS binding energies on the surface of KCPP, NCPP, MCPP, ZCPP, and SCPP samples before degradation.…”
Section: Analysis On Crystal Structure and Surface Composition Of Dopmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishikawa et al [5] injected a gelformed composite of collagen and powdered hydroxyapatite (C-HAp) into the bone tunnel to enhance healing between tendon and bone in an extra-articular animal model. The study showed that new bone formation and Sharpey's fibres emerging in the C-HAp group was much more than that in the control group before 8 weeks, but no Sharpey's fibres were observed [3]. Tien et al performed suspensory fixation ACL reconstruction in a rabbit model with special solubility calcium phosphate cement (CPC) to fill the gap between tendon and bone tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, much new bone formed in the samples not inhibited by McAb-BMP [24]. Concentration of the intrinsic biological signal (such as BMP) to the surface of porous calcium phosphate ceramics induced the mesenchymal cells to differentiate into preosteogenic cells [3]. The threedimensional porous structure and the formation of bonelike apatite interface provided a suitable environment for osteogenesis [3].…”
Section: Discussionmentioning
confidence: 99%